Formation of the Commercial Contract and the Problem of Risk. An essay on the American Legal Process. - Furnish, Dale Beck (1986)
The paper analyzes the formation of commercial contracts in the U.S. legal system, with a focus on the problem of risk. The author examines how contract theory has developed in the United States, from a rigid and formalistic view to a more flexible approach, embodied in the Uniform Commercial Code (UCC). It also discusses concepts such as “consideration” and its importance in validating a contract, as well as the exceptions to the general rule, such as “promissory estoppel”, which allows the fulfillment of promises without direct economic benefit. It also addresses the evolution of contracts in situations of risk, highlighting how the UCC allocates the risk of destruction of goods and the annulment of contracts for mutual mistake or frustration of purpose. All this, citing diverse case law referred to the implications of the commercial contract. Finally, he briefly explains the doctrine of unconscionability, which prohibits one of the parties to a business deal to take more advantage than necessary, which may mean the oppression of his counterpart with unfair surprises in the written agreement.